2017
DOI: 10.1111/pcn.12499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring psychiatric comorbidities and their effects on quality of life in patients with temporal lobe epilepsy and juvenile myoclonic epilepsy

Abstract: Our study suggests that comorbid psychiatric disorders negatively affect patients' QOL regardless of seizure syndrome. Comorbid psychiatric conditions should be determined to increase QOL in patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Epilepsy patients, including those with MTLE, experience many psychosocial problems, including depression, anxiety, and low self-esteem (Schiffer and Babigian, 1984;Tellez-Zenteno et al, 2007). Ertem et al (2017) detected comorbid psychiatric disorders in 57% of patients with MTLE. Similarly, Nogueira et al (2017) found that 39.6% of MTLE patients met diagnostic criteria for mood disorders and 34.7% of MTLE patients met diagnostic criteria for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy patients, including those with MTLE, experience many psychosocial problems, including depression, anxiety, and low self-esteem (Schiffer and Babigian, 1984;Tellez-Zenteno et al, 2007). Ertem et al (2017) detected comorbid psychiatric disorders in 57% of patients with MTLE. Similarly, Nogueira et al (2017) found that 39.6% of MTLE patients met diagnostic criteria for mood disorders and 34.7% of MTLE patients met diagnostic criteria for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Ertem et al assessed the effects of psychiatric comorbidity, demographic factors, and clinical features on QOL in patients with mesial temporal lobe epilepsy, juvenile myoclonic epilepsy, and healthy controls using the QOLIE-89. In their report, only psychiatric comorbidity in PWE affected QOL regardless of seizure syndrome 37 . Similar to our study, Chen et al explored the predictive factors of QOL in patients with TLE using the QOLIE-31 inventory 38 .…”
Section: Discussionmentioning
confidence: 86%
“…However, alterations involved in neural circuits considered as a primary suspect. In epilepsy due to abnormal functioning of brain electrical circuits have been attributed to ion channel mutations [7,8], therefore alterations in ion channel activity in relevant areas may also claimed in etiopathology of psychiatric disorders [9]. As mentioned in above case Oxcarbazepine and its metabolite 10-monohydroxy metabolite (MHD; in addition to its primary mechanism (i.e mechanism limiting the frequency of firing voltage dependent sodium channels) it might show clinically important effects on potassium channels [10][11][12].…”
Section: Discussionmentioning
confidence: 99%